Pharmacological Doses of Thiamine Benefit Patients with the Charcot–Marie–Tooth Neuropathy by Changing Thiamine Diphosphate Levels and Affecting Regulation of Thiamine-Dependent Enzymes - Artiukhov, Artem V.; Solovjeva, Olga N.; Balashova, Natalia V.; Sidorova, Olga P.; Graf, Anastasia V.; Bunik, Victoria I. (Biochemistry (Moscow), 2024)
Charcot–Marie–Tooth (CMT) neuropathy is a polygenic disorder of peripheral nerves with no effective cure. Thiamine (vitamin B1) is a neurotropic compound that improves neuropathies. Our pilot study characterizes therapeutic potential of daily oral administration of thiamine (100 mg) in CMT neuropathy and its molecular mechanisms. The patient hand grip strength was determined before and after thiamine administration along with the blood levels of the thiamine coenzyme form (thiamine diphosphate, ThDP), activities of endogenous holo-transketolase (without ThDP in the assay medium) and total transketolase (with ThDP in the assay medium), and transketolase activation by ThDP [1 – (holo-transketolase/total transketolase),%], corresponding to the fraction of ThDP-free apo-transketolase. Single cases of administration of sulbutiamine (200 mg) or benfotiamine (150 mg) reveal their effects on the assayed parameters within those of thiamine. Administration of thiamine or its pharmacological forms increased the hand grip strength in the CMT patients. Comparison of the thiamin status in patients with different forms of CMT disease to that of control subjects without diagnosed pathologies revealed no significant differences in the average levels of ThDP, holo-transketolase, or relative content of holo and apo forms of transketolase. However, the regulation of transketolase by thiamine/ThDP differed in the control and CMT groups: in the assay, ThDP activated transketolase from the control individuals, but not from CMT patients. Thiamine administration paradoxically decreased endogenous holo-transketolase in CMT patients; this effect was not observed in the control group. Correlation analysis revealed sex-specific differences in the relationship between the parameters of thiamine status in both the control subjects and patients with the CMT disease. Thus, our findings link physiological benefits of thiamine administration in CMT patients to changes in their thiamine status, in particular, the blood levels of ThDP and transketolase regulation.